LITERATURE REVIEW ANALYSIS OF ANTIOXIDANT ACTIVITY OF RED PIDADA LEAVES (Sonneratia Caseolaris L) USING A SPECTROPHOTOMETER - Rahmah, Siti; Bii, Maria Febriani Wea; Permatasari, Nurfebby; Saputra, Juliansyah Yugis; Halitopo, Maria Ratu F.; Agustin, Tasya; Gledys, Juliana; Purnama, Maya (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2025)
This study aimed to evaluate the antioxidant activity and toxicity of the ethanolic extract of red mangrove leaves (Sonneratia caseolaris). Extraction was conducted by maceration using 96% ethanol. Antioxidant activity was tested using the DPPH and ABTS methods with vitamin C as a reference, while toxicity was determined through the Brine Shrimp Lethality Test (BSLT). The extract showed very strong antioxidant activity with IC50 values of 37.67 ppm (ABTS) and 4.25 ± 3.05 ppm (DPPH). LC-HRMS identified TEMPO, Choline, and Betaine, with TEMPO showing the highest antioxidant potential. The BSLT result indicated non-toxic properties (LC50 >1500 ppm). The extract shows promise as a safe and effective natural antioxidant source.